Pembinaan Disiplin Kerja Pegawai Di Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Sanggau - Marcselly Romauli Siahaan; Yulius Yohanes; Mukhlis Mukhlis (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the discipline training of Civil Servants (ASN) at the Personnel and Human Resources Development Agency (BKPSDM) of Sanggau Regency. Discipline training is considered a critical step to improve employee performance and public service delivery. This research employs a qualitative descriptive method with data collection techniques including interviews, observations, and documentation. The main focus of the study is to examine the implementation of discipline training and identify the supporting and inhibiting factors in the policy's execution.The results reveal that discipline training at BKPSDM Sanggau Regency has not been fully optimized. Discipline violations, such as non-compliance with working hours and neglect of duties, remain common. Major challenges in implementing discipline training include weak supervision, lack of employee motivation, and limited resources, such as budget and facilities. However, the commitment of agency leaders and support from bureaucratic reform policies are significant supporting factors in enhancing employee discipline.As recommendations, this study suggests increasing the budget for discipline training programs, providing training for leaders and employees, and improving the availability of adequate facilities. Additionally, periodic evaluations of discipline training policies should be conducted to ensure their effectiveness. This research is expected to contribute to the development of public administration science and serve as a reference for local governments in establishing good governance practices.